EFEKTIVITAS PENYERAPAN ANGGARAN PADA MINISTÉRIO DAS OBRAS PÚBLICAS TIMOR LESTE - AMARAL, JOÃO; WIAGUSTINI, LUH PUTU (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.08.NO.02.TAHUN 2019DO - 10.24843/EEB.2019.v08.i02.p01, 2019)
The purpose of this study was to investigate to know and analyze the   effectiveness of budget absorption at the Ministry of Public Works in East Timor. This study was conducted to assist the Directorate of Public Works in East Timor, as the basis for decision-making and evaluation of budget absorption, also contribute to science in terms of the absorption of the government budget. This study uses the data collection techniques the Documentation that the data collected through the existing budget documents in the Ministry of Public Works in the State of Timor Leste. Documents such as financial reports comprise the budget from 2009 - 2013. The Data was processed with descriptive approach is by using a ratio of budget  effectiveness ratio of the budget, where the results of the two ratios Compared to the standard budget applicable at the Government of Timor-Leste. The results showed average effectiveness of the budget from 2009 to 2013 amounted to 89.29% with the percentage 80%-90% or categorized   Effectiveness. This shows that the financial performance in terms of absorption of Timor Leste Ministry of Public Works in 2009 to 2013 are   good.